Profil Kemampuan Literasi Matematis Siswa Kelas VII di SMP Negeri 9 Singkawang - Pratiwi Ayutias; Nurul Husna; Buyung Buyung (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study aims to: 1) Describe the profile of students' mathematical literacy abilities in the personal context domain in solving algebra problems based on components in class VII students of SMP Negeri 9 Singkawang in the 2020/2021 academic year; 2) Describe the profile of students' mathematical literacy abilities in the personal context domain in solving algebra problems based on components in class VII students of SMP Negeri 9 Singkawang in the 2020/2021 academic year; 3) Describe the profile of students' mathematical literacy abilities in the personal context domain in solving algebra problems based on components in class VII students of SMP Negeri 9 Singkawang in the 2020/2021 academic year. This research method is a qualitative research method. The subjects in this study were 30 class VII A students. The object of this study is mathematical literacy abilities in algebra material. The data collection instruments were written tests and interviews in accordance with the strategic competency indicators that had been tested with content validity, construct validity, reliability, level of difficulty and discriminatory power. The results of the study showed that: 1) Of the 30 students who took the mathematical literacy ability test, in the personal context domain the average student score was 45.83 and was in the moderate category; 2) Of the 30 students who took the mathematical literacy ability test, in the work context domain the average student score was 57.22 and was in the moderate category; 3) Of the 30 students who took the mathematical literacy ability test, in the general context domain the average student score was 54.44 and was in the moderate category.